Gerakan Persaudaraan Muslimah (Salimah) dalam Memberi Pendidikan Keluarga Kepada Masyarakat - Rahayu Apridayanti; Muhammad Ghozali; Eka Ariskawanti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Family education is a solution to condition the crisis of character values in the now progressive generation. The implementation of an educational civilization development organization is now a hope for the future of every individual's life. The Muslim Brotherhood Organization (Salimah) is an organization that is engaged in transferring knowledge and skills as a form of community service. The study used descriptive qualitative methods with the method of collecting observational data on an object of research and supported by information from sources (research subjects). The purpose of the study was to find out the role of Salimah in providing educational values to the community. The results found that the role of the program that was echoed by Salimah in encouraging education for the community was